1996
DOI: 10.1042/bj3140613
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the 5′ end and promoter region of the chicken acetyl-CoA carboxylase gene

Abstract: Acetyl-CoA carboxylase is a rate-limiting enzyme in the biogenesis of long-chain fatty acids. In the present study, the 5h end and flanking region of the acetyl-CoA carboxylase (ACC) gene was analysed in the chicken. A genomic clone was isolated containing the first three exons, the third one containing the ATG codon. Using nuclease-mapping experiments and primerextension analyses, the transcription-initiation site was located 153 nucleotides upstream of the ATG codon. In contrast with rat ACC gene expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Sequences corresponding to E4 are well conserved from chicken to man and alternative exon splicing of E4 has been demonstrated in a number of species , Ha et al 1994, Barber & Travers 1995. In contrast to our findings in ovine adipose tissue, in which transcripts that lack E4 predominate, the majority of ACC-transcripts in rat tissues, including adipose tissue (LopezCasillas et al 1991) and in chicken liver appear to include E4 (El Khadir-Mounier et al 1996). Thus, the significance of transcript heterogeneity due to the inclusion or exclusion of E4 in ACC-mRNA is unclear at present and remains to be determined.…”
Section: Discussioncontrasting
confidence: 55%
“…Sequences corresponding to E4 are well conserved from chicken to man and alternative exon splicing of E4 has been demonstrated in a number of species , Ha et al 1994, Barber & Travers 1995. In contrast to our findings in ovine adipose tissue, in which transcripts that lack E4 predominate, the majority of ACC-transcripts in rat tissues, including adipose tissue (LopezCasillas et al 1991) and in chicken liver appear to include E4 (El Khadir-Mounier et al 1996). Thus, the significance of transcript heterogeneity due to the inclusion or exclusion of E4 in ACC-mRNA is unclear at present and remains to be determined.…”
Section: Discussioncontrasting
confidence: 55%
“…However, no complete structures of the genes for any of the mammalian biotin carboxylases have yet been published. Only two studies have reported the isolation of the 5Ј non-coding exons of rat and chicken acetyl-CoA carboxylase genes (28,29), thus limiting the comparison of our data for genomic structures to those enzymes.…”
Section: Organization Of the Coding Exons-mentioning
confidence: 94%
“…The sequence of the primers used to generate the Ϫ1500 to Ϫ855 bp fragment was derived from the published ACC␣ promoter 2 sequence (38). ACC␣ DNA fragments used to construct reporter plasmids were named by designating the 5Ј-and 3Ј-ends of each fragment relative to the transcription start site.…”
Section: Methodsmentioning
confidence: 99%